An ecological self-hardening furan resin with controllable curing speed
By introducing composite photosensitizers and aldehyde reducing agents into the furan resin, the ecological self-hardening furan resin with controllable curing speed is solved, and the existing resins have poor mechanical properties and curing speed and high free formaldehyde content are achieved, thereby achieving efficient curing of the resin and improving environmental protection performance.
Patent Information
- Application Number
- CN202411300235.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The mechanical properties and curing speed of existing furan resins are poor, and the free formaldehyde content is high, resulting in environmental pollution and human health threats.
Using composite photosensitizers and aldehyde reducing agents, an ecologically self-hardening furan resin with controllable curing speed is synthesized through specific process steps. The resin consists of furfuryl alcohol, formaldehyde, urea, composite photosensitizer, aldehyde reducing agent, silane coupling agent, sodium hydroxide, hydrochloric acid and nanosilica. By adjusting the reaction conditions and additive ratio, the resin can be controlled cured and the free formaldehyde content are achieved.
The controlled curing speed of ecological self-hardening furan resin is achieved, the mechanical properties of the resin are improved, and the content of free formaldehyde is significantly reduced, and environmental pollution and human health risks are reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-hardening furan resin preparation, and in particular relates to an ecological self-hardening furan resin with controllable curing speed. Background Art
[0002] In the current context where environmental protection and resource conservation are increasingly valued, traditional resin materials are often accompanied by high energy consumption and environmental pollution during the curing process, which makes the development of new environmentally friendly resin materials a hot topic in the field of materials science.
[0003] As an important polymer material, furan resin has been widely used in casting, construction, aerospace and other fields due to its excellent physical properties and chemical stability. However, the curing speed of traditional furan resin is difficult to control, and harmful gases and waste are easily generated during the curing process, posing a potential threat to the environment and human health. Therefore, the development of an ecological self-hardening furan resin with controllable curing speed and good environmental performance has important practical significance and broad application prospects.
[0004] Patent CN 104448179 B discloses a graphene-modified furan resin and a preparation method thereof, wherein the graphene-modified furan resin is prepared from an acidic catalyst, a graphene dispersant, furfural and furfural ketone; the graphene dispersant includes graphene and furfuryl alcohol. The preparation method comprises the following steps: mixing graphene and furfuryl alcohol to obtain a graphene dispersant; reacting the graphene dispersant, furfural and furfuryl ketone under acidic conditions to obtain a graphene-modified furan resin. The obtained graphene-modified furan resin has lower brittleness and lower formaldehyde content. However, the mechanical properties and curing speed of the resin prepared by this method are not good, and there is still room for reducing the free formaldehyde content. Summary of the invention
[0005] The purpose of the present invention is to provide an ecological self-hardening furan resin with controllable curing speed, so as to solve the technical problems of the furan resin in the prior art, such as poor mechanical properties, poor curing speed and high free formaldehyde content.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides an ecological self-hardening furan resin with controllable curing speed. The resin is composed of the following components in parts by weight: 35-42 parts of furfuryl alcohol, 10-30 parts of formaldehyde, 2-8 parts of urea, 1-5 parts of a composite photosensitizer, 1-3 parts of a formaldehyde reducing agent, 0.2-0.5 parts of a silane coupling agent, 0.2-0.4 parts of sodium hydroxide, 0.1-0.3 parts of hydrochloric acid, and 2-4 parts of nano silicon dioxide. The composite photosensitizer is prepared from dibromotriphenylamine, bipyraclostrobin, 1-(4-bromophenyl)-pyrrolidine, malononitrile, sodium lignin sulfonate, potassium persulfate, methyl allyl polyoxyethylene ether, and dodecyl dimethyl benzyl ammonium chloride, and the formaldehyde reducing agent is prepared from corn starch under the conditions that copper sulfate pentahydrate is used as a catalyst and potassium permanganate is used as an oxidant.
[0008] Preferably, the method for preparing the composite photosensitizer comprises the following steps:
[0009] Q1: Under an argon atmosphere, phosphorus oxychloride was slowly added dropwise to N,N-dimethylformamide, the mixture was placed at room temperature and continued to be stirred, then dibromotriphenylamine was added, the temperature was raised to reflux, and after completion, the mixture was cooled, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1;
[0010] Q2: Under an argon atmosphere, add pinacol diboronate, 1-(4-bromophenyl)-pyrrolidine, potassium acetate and DPPF palladium dichloride to 1,4-dioxane in sequence, heat to reflux, cool, extract, dry, reduce pressure, elute, separate and purify to obtain intermediate product 2; under an argon atmosphere, mix intermediate product 1, intermediate product 2, DPPF palladium dichloride, cesium carbonate and anhydrous 1,4-dioxane, heat to reflux, cool, extract, elute, separate and purify to obtain intermediate product 3; under an argon atmosphere, add intermediate product 3 and malononitrile to dichloromethane, and simultaneously add triethylamine dropwise, heat the obtained mixture to reflux, elute, separate and purify to obtain intermediate product 4;
[0011] Q3: Sodium lignin sulfonate was dissolved in distilled water and added to a three-necked flask connected to a constant pressure dropping funnel. A potassium persulfate aqueous solution and a methyl allyl polyoxyethylene ether aqueous solution were added to the constant pressure dropping funnel respectively. The joints were sealed to form a closed experimental environment. Argon gas was replaced through a double row of tubes. Condensed water was introduced into the reaction device. The temperature was raised with stirring. Then, the potassium persulfate aqueous solution was added dropwise. After the addition was completed, the temperature was raised and the methyl allyl polyoxyethylene ether aqueous solution was added dropwise. After the addition was completed, the reaction was carried out. After the reaction was completed, isopropanol was added to quench the reaction. The reaction was purified to obtain an intermediate product 5.
[0012] Q4: Add dodecyldimethylbenzyl ammonium chloride to deionized water for dissolution, pour into a container, then dissolve the intermediate product 5 in deionized water, slowly drop into the container, stir after the addition is complete, let stand to react, remove the supernatant, filter, wash, and vacuum dry to obtain the intermediate product 6; mix the intermediate product 4 and the intermediate product 6 to obtain a composite photosensitizer.
[0013] In the above process, phosphorus oxychloride, dibromotriphenylamine, bipyraclostrobin and 1-(4-bromophenyl)-pyrrolidine are used as raw materials to synthesize intermediate product 4, and then methyl allyl polyoxyethylene ether is used as a monomer and potassium persulfate is used as an initiator to graft and copolymerize sodium lignin sulfonate through aqueous solution polymerization to obtain intermediate product 5, and dodecyl dimethyl benzyl ammonium chloride is used to electrostatically self-assemble intermediate product 5 to obtain intermediate product 6, and intermediate product 4 with photosensitivity function and intermediate product 6 with dispersion function are mixed to obtain a composite photosensitizer. The synthesis process of intermediate product 4 is as follows:
[0014]
[0015] The results of mass spectrometry analysis were: m / z: 611.30 (100.0%), 612.31 (45.9%), 613.31 (11.1%), 612.30 (1.8%), 614.31 (1.6%).
[0016] Preferably, in Q1, the molar ratio of phosphorus oxychloride, N,N-dimethylformamide and dibromotriphenylamine is (8.94-13.41): (21.55-32.33): (1-1.5), the temperature of N,N-dimethylformamide is 0-1°C, the stirring time is 1-2h, the reflux temperature is 100-110°C, the time is 5-7h, and the cooling time is 30-40min; in Q2, the molar ratio of diboric acid pinacol ester, 1-(4-bromophenyl)-pyrrolidine, potassium acetate and DPPF palladium dichloride is (2-4 ):(1-2):(2-4):(3.3-6.6), the heating reflux temperature is 110-120°C, the time is 20-24h, the molar ratio of intermediate 1, intermediate 2, DPPF palladium dichloride and cesium carbonate is (1-2):(2.2-4.4):(0.1-0.2):(0.6-1.2), the heating reflux temperature is 90-100°C, the time is 18-20h, the molar ratio of intermediate 3 and malononitrile is (1-2):(1-2), the heating reflux temperature is 40-50°C, and the time is 2-3h.
[0017] Preferably, in Q3, the dosage ratio of sodium lignin sulfonate, distilled water, potassium persulfate aqueous solution and methyl allyl polyoxyethylene ether aqueous solution is (10-12) g: (50-60) mL: (20-25) mL: (20-25) mL, the concentration of potassium persulfate aqueous solution is 0.020 g / mL, the concentration of methyl allyl polyoxyethylene ether aqueous solution is 0.213 g / mL, the heating and stirring temperature is 50-60°C, the time is 20-30 min, the time for adding potassium persulfate aqueous solution is 30-35 min, the heating temperature is 70-80°C, the time for adding methyl allyl polyoxyethylene ether aqueous solution is 25-30 min, and the reaction time is 3-5 h.
[0018] Preferably, in Q4, the mass ratio of dodecyldimethylbenzylammonium chloride and intermediate product 5 is (0.80-1.00): (1.01-1.26), the dropping time is 30-40 min, the stirring time is 30-40 min, the standing time is 48-50 h, the vacuum drying temperature is 40-50 ° C, the time is 20-24 h, the pressure is -0.1~-0.08 MPa, the mass ratio of intermediate product 4 and intermediate product 6 is (2-5): (0.8-0.9), and the mixing time is 2-3 h.
[0019] Preferably, the preparation method of the aldehyde reducing agent comprises the following steps:
[0020] S1: Add corn starch to distilled water and stir to obtain corn starch emulsion, then transfer it completely to a three-necked flask with a constant pressure dropping funnel and a thermometer, and place the beaker in a constant temperature water bath for constant temperature treatment to obtain a viscous emulsion;
[0021] S2: Add copper sulfate pentahydrate to the viscous emulsion, adjust the pH and then add potassium permanganate dropwise, react at a constant temperature, adjust the pH, filter, wash, and vacuum dry to obtain a formaldehyde reducing agent.
[0022] In the above process, corn starch is selected as raw material, potassium permanganate is used as oxidant, copper sulfate pentahydrate is used as reaction catalyst, and the formaldehyde reducing agent is prepared by the traditional wet synthesis method.
[0023] Preferably, in S1, the dosage ratio of corn starch to distilled water is (10-13) g: (50-60) mL, the stirring time is 30-40 min, the constant temperature treatment temperature is 50-60°C, and the treatment time is 10-30 min; in S2, the dosage ratio of copper sulfate pentahydrate to potassium permanganate is (0.3-0.5) g: (8-10) mL, the pH is adjusted to 7-7.5, the constant temperature reaction temperature is 50-60°C, the time is 2-3 h, and then the pH is adjusted to 6-6.5, and the vacuum drying temperature is 50-60°C.
[0024] Preferably, the method for preparing the ecological self-hardening furan resin with controllable curing speed comprises the following steps:
[0025] Step (1): heating formaldehyde and a silane coupling agent for mixed reaction, then adding urea, adjusting the pH with sodium hydroxide, heating to continue the reaction, then adding furfuryl alcohol, adjusting the pH with hydrochloric acid, and continuing the heating to react to obtain a mixed reactant;
[0026] Step (2): adding a composite photosensitizer, a formaldehyde reducing agent and nano-silicon dioxide to the mixed reactants, stirring and reacting, and obtaining an ecological self-hardening furan resin with controllable curing speed.
[0027] Preferably, in the step (1), the heating and mixing reaction temperature is 40-60°C, the time is 20-40 min, the pH is adjusted to 8-10, the heating and continued reaction temperature is 70-90°C, the time is 30-45 min, the pH is adjusted to 3-5, the heating and continued reaction temperature is 80-120°C, and the time is 40-60 min; in the step (2), the stirring reaction time is 3-5 h.
[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0029] 1. The present invention firstly uses dibromotriphenylamine, bipyraclostrobin, 1-(4-bromophenyl)-pyrrolidine, sodium lignin sulfonate, methyl allyl polyoxyethylene ether and dodecyl dimethyl benzyl ammonium chloride as raw materials to synthesize a composite photosensitizer with excellent dispersibility, then uses corn starch, potassium permanganate and copper sulfate pentahydrate as raw materials to synthesize a formaldehyde reducing agent, and adds the composite photosensitizer and the formaldehyde reducing agent to an ecological self-hardening furan resin, so that the resin can have a controllable curing speed and can also reduce the content of free formaldehyde. At the same time, the nano silicon dioxide added in the preparation process can also increase the mechanical properties of the ecological self-hardening furan resin.
[0030] 2. The present invention uses dibromotriphenylamine, bipyraclostrobin, 1-(4-bromophenyl)-pyrrolidine and sodium lignin sulfonate as raw materials to synthesize a composite photosensitizer, which is added to an ecological self-hardening furan resin to allow the resin to have a controllable curing speed. The intermediate product 4 obtained can absorb light energy and convert it into chemical energy under light conditions to produce active substances such as free radicals or ions. The presence of the active substances can trigger or accelerate polymerization or cross-linking reactions in the resin, thereby affecting the curing speed of the resin; the intermediate product 6 obtained can improve the dispersibility of the composite photosensitizer in the resin, making it more evenly distributed in the resin, which helps the composite photosensitizer to absorb light energy more effectively and produce active substances, thereby increasing the curing speed of the resin; the synergistic effect between the two allows the composite photosensitizer to be evenly dispersed in the resin, thereby allowing the ecological self-hardening furan resin to have a controllable curing speed.
[0031] 3. The present invention uses corn starch and potassium permanganate as raw materials and obtains a formaldehyde reducing agent through a traditional wet synthesis method. When the formaldehyde reducing agent contacts free formaldehyde in ecological self-hardening furan resin, potassium permanganate can rapidly oxidize the aldehyde groups in the formaldehyde molecules and convert them into formic acid or carbon dioxide and water, thereby reducing the concentration of free formaldehyde in the resin. Corn starch is a polysaccharide polymer compound, and its molecular chain contains multiple hydroxyl groups, which are hydrophilic. During the wet synthesis process, corn starch molecules will form a certain spatial structure or network structure, which can adsorb and fix free formaldehyde molecules in the resin, thereby reducing the concentration of free formaldehyde through adsorption. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0033] This embodiment discloses a method for preparing a composite photosensitizer, comprising the following steps:
[0034] Q1: Under argon atmosphere, 7.5 mL of phosphorus oxychloride was slowly added dropwise to 15 mL of N,N-dimethylformamide at 0°C, the mixture was placed at room temperature and stirred for 2 h, then 3.63 g of dibromotriphenylamine was added, and the mixture was heated to 110°C and refluxed for 7 h. After the reaction, the mixture was cooled for 35 min, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1;
[0035] Q2: Under argon atmosphere, 7.62g of diboronic acid pinacol ester, 3.39g of 1-(4-bromophenyl)-pyrrolidine, 2.94g of potassium acetate and 0.336g of DPPF palladium dichloride were added to 50mL of 1,4-dioxane in sequence, heated to reflux at 120°C for 24h, cooled, extracted, dried, reduced pressure, eluted, separated and purified to obtain intermediate 2; under argon atmosphere, 0.96g of intermediate 1, 1.35g of intermediate 2 and 0.162g of DPPF palladium dichloride, 4.35 g cesium carbonate and 20 mL anhydrous 1,4-dioxane were mixed, heated at 90°C for 20 h, cooled, extracted, eluted, separated and purified to obtain intermediate product 3; under argon atmosphere, 2.1 g intermediate product 3 and 0.6 g malononitrile were added to 20 mL dichloromethane, and 0.025 mL triethylamine was added dropwise, and the obtained mixture was heated at 50°C for 3 h, eluted, separated and purified to obtain intermediate product 4;
[0036] Q3: After dissolving 11g of sodium lignin sulfonate in 55mL of distilled water, add the solution to a three-necked flask connected to a constant pressure dropping funnel, add 22.5mL of 0.020g / mL potassium persulfate aqueous solution and 22.5mL of 0.213g / mL methyl allyl polyoxyethylene ether aqueous solution to the constant pressure dropping funnel respectively, seal the joints to form a closed experimental environment, replace the argon gas through a double row of tubes, pass condensed water into the reaction device, heat to 60℃ and stir for 30min, then add potassium persulfate aqueous solution dropwise for 30min, after the addition is complete, heat to 75℃, add methyl allyl polyoxyethylene ether aqueous solution dropwise for 25min, after the addition is complete, react for 5h, after the reaction is complete, add isopropanol to quench the reaction, purify, and obtain intermediate 5;
[0037] Q4: Add 0.9 g of dodecyldimethylbenzyl ammonium chloride into 20 mL of deionized water for dissolution, pour into a container, then dissolve 1.13 g of intermediate product 5 in 20 mL of deionized water, and slowly add it dropwise to the container for 35 min. After the addition is complete, stir for 40 min, let stand for 48 h, remove the supernatant, filter, wash, and vacuum dry at 50 ° C and -0.1 MPa for 24 h to obtain intermediate product 6; 3.5 g of intermediate product 4 and 0.85 g of intermediate product 6 are mixed for 3 h to obtain a composite photosensitizer.
[0038] This embodiment discloses a method for preparing an aldehyde reducing agent, comprising the following steps:
[0039] S1: Add 11.5 g corn starch to 55 mL distilled water and stir for 40 min to obtain a corn starch emulsion, then transfer it completely to a three-necked flask with a constant pressure dropping funnel and a thermometer, and place the beaker in a constant temperature water bath at 60 ° C for 30 min to obtain a viscous emulsion;
[0040] S2: Add 0.4 g of copper sulfate pentahydrate to the viscous emulsion, adjust the pH to 7, then add 9 mL of potassium permanganate dropwise, react at 60°C for 3 h, adjust the pH to 6, filter, wash, and vacuum dry at 60°C to obtain a formaldehyde reducing agent.
[0041] The present embodiment discloses an ecological self-hardening furan resin with controllable curing speed, which is composed of the following components in parts by weight: 37.5 parts of furfuryl alcohol, 20 parts of formaldehyde, 5 parts of urea, 3 parts of composite photosensitizer, 2 parts of formaldehyde reducing agent, 0.35 parts of silane coupling agent G-570, 0.3 parts of sodium hydroxide, 0.2 parts of hydrochloric acid, and 3 parts of nano silicon dioxide (Shanghai Yuanye Biotechnology Co., Ltd.).
[0042] This embodiment discloses a method for preparing an ecological self-hardening furan resin with controllable curing speed, comprising the following steps:
[0043] Step (1): heating formaldehyde and silane coupling agent G-570 at 60°C for 40 minutes, then adding urea, adjusting pH to 8 with sodium hydroxide, heating at 80°C for 45 minutes, then adding furfuryl alcohol, adjusting pH to 3 with hydrochloric acid, and heating at 110°C for 60 minutes to obtain a mixed reactant;
[0044] Step (2): Add a composite photosensitizer, a formaldehyde reducing agent and nano-silica to the mixed reactants, stir and react for 5 hours, and obtain an ecological self-hardening furan resin with controllable curing speed. Example 2
[0045] This embodiment discloses a method for preparing a composite photosensitizer, comprising the following steps:
[0046] Q1: Under argon atmosphere, 5 mL of phosphorus oxychloride was slowly added dropwise to 20 mL of N,N-dimethylformamide at 0°C, the mixture was placed at room temperature and stirred for 2 h, then 2.42 g of dibromotriphenylamine was added, and the mixture was heated to 110°C and refluxed for 7 h. After the reaction, the mixture was cooled for 35 min, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1;
[0047] Q2: Under argon atmosphere, 5.08 g of diboronic acid pinacol ester, 2.26 g of 1-(4-bromophenyl)-pyrrolidine, 1.96 g of potassium acetate and 0.448 g of DPPF palladium dichloride were added to 50 mL of 1,4-dioxane in sequence, heated to reflux at 120 ° C for 24 h, cooled, extracted, dried, reduced pressure, eluted, separated and purified to obtain intermediate 2; under argon atmosphere, 0.64 g of intermediate 1, 0.9 g of intermediate 2 and 0.108 g of DPPF palladium dichloride, 2.9 g cesium carbonate and 20 mL anhydrous 1,4-dioxane were mixed, heated at 90°C for 20 h, cooled, extracted, eluted, separated and purified to obtain intermediate product 3; under argon atmosphere, 1.4 g intermediate product 3 and 0.4 g malononitrile were added to 20 mL dichloromethane, and 0.025 mL triethylamine was added dropwise, and the obtained mixture was heated at 50°C for 3 h, eluted, separated and purified to obtain intermediate product 4;
[0048] Q3: After dissolving 10g of sodium lignin sulfonate in 50mL of distilled water, add it to a three-necked flask connected to a constant pressure dropping funnel, add 20mL of 0.020g / mL potassium persulfate aqueous solution and 25mL of 0.213g / mL methyl allyl polyoxyethylene ether aqueous solution to the constant pressure dropping funnel respectively, seal the joints to form a closed experimental environment, replace argon through a double row of tubes, pass condensed water into the reaction device, heat to 60℃ and stir for 30min, then add potassium persulfate aqueous solution dropwise for 30min, after the addition is complete, heat to 75℃, add methyl allyl polyoxyethylene ether aqueous solution dropwise for 25min, after the addition is complete, react for 5h, after the reaction is complete, add isopropanol to quench the reaction, purify, and obtain intermediate 5;
[0049] Q4: Add 0.8 g of dodecyldimethylbenzyl ammonium chloride into 20 mL of deionized water for dissolution, pour into a container, then dissolve 1.01 g of intermediate product 5 in 20 mL of deionized water, and slowly add it dropwise to the container for 35 min. After the addition is complete, stir for 40 min, let stand for 48 h, remove the supernatant, filter, wash, and vacuum dry at 50 ° C and -0.1 MPa for 24 h to obtain intermediate product 6; mix 2 g of intermediate product 4 and 0.8 g of intermediate product 6 for 3 h to obtain a composite photosensitizer.
[0050] This embodiment discloses a method for preparing an aldehyde reducing agent, comprising the following steps:
[0051] S1: Add 10 g corn starch to 50 mL distilled water and stir for 40 min to obtain corn starch emulsion, then transfer it completely to a three-necked flask with a constant pressure dropping funnel and a thermometer, and place the beaker in a constant temperature water bath at 60 ° C for 30 min to obtain a viscous emulsion;
[0052] S2: Add 0.3 g of copper sulfate pentahydrate to the viscous emulsion, adjust the pH to 7, then add 10 mL of potassium permanganate dropwise, react at 60°C for 3 h, adjust the pH to 6, filter, wash, and vacuum dry at 60°C to obtain a formaldehyde reducing agent.
[0053] The present embodiment discloses an ecological self-hardening furan resin with controllable curing speed, which is composed of the following components in parts by weight: 35 parts of furfuryl alcohol, 10 parts of formaldehyde, 2 parts of urea, 1 part of composite photosensitizer, 1 part of formaldehyde reducing agent, 0.2 parts of silane coupling agent G-570, 0.2 parts of sodium hydroxide, 0.1 parts of hydrochloric acid, and 2 parts of nano silicon dioxide (Shanghai Yuanye Biotechnology Co., Ltd.).
[0054] This embodiment discloses a method for preparing an ecological self-hardening furan resin with controllable curing speed, comprising the following steps:
[0055] Step (1): heating formaldehyde and silane coupling agent G-570 at 60°C for 40 minutes, then adding urea, adjusting pH to 8 with sodium hydroxide, heating at 80°C for 45 minutes, then adding furfuryl alcohol, adjusting pH to 3 with hydrochloric acid, and heating at 110°C for 60 minutes to obtain a mixed reactant;
[0056] Step (2): Add a composite photosensitizer, a formaldehyde reducing agent and nano-silica to the mixed reactants, stir and react for 5 hours, and obtain an ecological self-hardening furan resin with controllable curing speed. Example 3
[0057] This embodiment discloses a method for preparing a composite photosensitizer, comprising the following steps:
[0058] Q1: Under argon atmosphere, 10 mL of phosphorus oxychloride was slowly added dropwise to 10 mL of N,N-dimethylformamide at 0°C, the mixture was placed at room temperature and stirred for 2 h, then 4.84 g of dibromotriphenylamine was added, and the mixture was heated to 110°C and refluxed for 7 h. After the reaction, the mixture was cooled for 35 min, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1;
[0059] Q2: Under argon atmosphere, 10.16 g of diboronic acid pinacol ester, 4.52 g of 1-(4-bromophenyl)-pyrrolidine, 3.92 g of potassium acetate and 0.224 g of DPPF palladium dichloride were added to 50 mL of 1,4-dioxane in sequence, heated to reflux at 120 ° C for 24 h, cooled, extracted, dried, reduced pressure, eluted, separated and purified to obtain intermediate 2; under argon atmosphere, 1.28 g of intermediate 1, 1.8 g of intermediate 2, and 0.216 g of DPPF palladium dichloride, 5.8 g cesium carbonate and 20 mL anhydrous 1,4-dioxane were mixed, heated at 90°C for 20 h, cooled, extracted, eluted, separated and purified to obtain intermediate product 3; under argon atmosphere, 2.8 g intermediate product 3 and 0.8 g malononitrile were added to 20 mL dichloromethane, and 0.025 mL triethylamine was added dropwise, and the obtained mixture was heated at 50°C for 3 h, eluted, separated and purified to obtain intermediate product 4;
[0060] Q3: After dissolving 12g of sodium lignin sulfonate in 60mL of distilled water, add the solution to a three-necked flask connected to a constant pressure dropping funnel, add 25mL of 0.020g / mL potassium persulfate aqueous solution and 20mL of 0.213g / mL methyl allyl polyoxyethylene ether aqueous solution to the constant pressure dropping funnel respectively, seal the joints to form a closed experimental environment, replace the argon gas through a double row of tubes, pass condensed water into the reaction device, heat to 60℃ and stir for 30min, then add potassium persulfate aqueous solution dropwise for 30min, after the addition is complete, heat to 75℃, add methyl allyl polyoxyethylene ether aqueous solution dropwise for 25min, after the addition is complete, react for 5h, after the reaction is complete, add isopropanol to quench the reaction, purify, and obtain intermediate 5;
[0061] Q4: Add 1g of dodecyldimethylbenzyl ammonium chloride into 20mL of deionized water to dissolve it, then pour it into a container, then dissolve 1.26g of intermediate product 5 in 20mL of deionized water, and slowly add it dropwise to the container for 35min. After the addition is complete, stir for 40min, let it stand for 48h, remove the supernatant, filter, wash, and vacuum dry at 50℃ and -0.1MPa for 24h to obtain intermediate product 6; mix 5g of intermediate product 4 and 0.9g of intermediate product 6 for 3h to obtain a composite photosensitizer.
[0062] This embodiment discloses a method for preparing an aldehyde reducing agent, comprising the following steps:
[0063] S1: Add 13 g corn starch to 60 mL distilled water and stir for 40 min to obtain corn starch emulsion, then transfer it completely to a three-necked flask with a constant pressure dropping funnel and a thermometer, and place the beaker in a constant temperature water bath at 60 ° C for 30 min to obtain a viscous emulsion;
[0064] S2: Add 0.5 g of copper sulfate pentahydrate to the viscous emulsion, adjust the pH to 7, then add 8 mL of potassium permanganate dropwise, react at 60°C for 3 h, adjust the pH to 6, filter, wash, and vacuum dry at 60°C to obtain a formaldehyde reducing agent.
[0065] The present embodiment discloses an ecological self-hardening furan resin with controllable curing speed, which is composed of the following components in parts by weight: 42 parts of furfuryl alcohol, 30 parts of formaldehyde, 8 parts of urea, 5 parts of composite photosensitizer, 3 parts of formaldehyde reducing agent, 0.5 parts of silane coupling agent G-570, 0.4 parts of sodium hydroxide, 0.3 parts of hydrochloric acid, and 4 parts of nano silicon dioxide (Shanghai Yuanye Biotechnology Co., Ltd.).
[0066] This embodiment discloses a method for preparing an ecological self-hardening furan resin with controllable curing speed, comprising the following steps:
[0067] Step (1): heating formaldehyde and silane coupling agent G-570 at 60°C for 40 minutes, then adding urea, adjusting pH to 8 with sodium hydroxide, heating at 80°C for 45 minutes, then adding furfuryl alcohol, adjusting pH to 3 with hydrochloric acid, and heating at 110°C for 60 minutes to obtain a mixed reactant;
[0068] Step (2): Add a composite photosensitizer, a formaldehyde reducing agent and nano-silica to the mixed reactants, stir and react for 5 hours, and obtain an ecological self-hardening furan resin with controllable curing speed. Example 4
[0069] This embodiment discloses a method for preparing a composite photosensitizer, comprising the following steps:
[0070] Q1: Under argon atmosphere, 6 mL of phosphorus oxychloride was slowly added dropwise to 16 mL of N,N-dimethylformamide at 0°C, the mixture was placed at room temperature and stirred for 2 h, then 3.07 g of dibromotriphenylamine was added, and the mixture was heated to 110°C and refluxed for 7 h. After the reaction, the mixture was cooled for 35 min, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1;
[0071] Q2: Under argon atmosphere, 8.37 g of biboronic acid pinacol ester, 3.18 g of 1-(4-bromophenyl)-pyrrolidine, 2.73 g of potassium acetate and 0.315 g of DPPF palladium dichloride were added to 50 mL of 1,4-dioxane in sequence, heated to reflux at 120 ° C for 24 h, cooled, extracted, dried, reduced pressure, eluted, separated and purified to obtain intermediate 2; under argon atmosphere, 0.83 g of intermediate 1, 1.6 g of intermediate 2, and 0.143 g of DPPF palladium dichloride, 4.17 g cesium carbonate and 20 mL anhydrous 1,4-dioxane were mixed, heated at 90°C for 20 h, cooled, extracted, eluted, separated and purified to obtain intermediate product 3; under argon atmosphere, 1.8 g intermediate product 3 and 0.7 g malononitrile were added to 20 mL dichloromethane, and 0.025 mL triethylamine was added dropwise, and the obtained mixture was heated at 50°C for 3 h, eluted, separated and purified to obtain intermediate product 4;
[0072] Q3: After dissolving 10.5g of sodium lignin sulfonate in 53mL of distilled water, add the solution to a three-necked flask connected to a constant pressure dropping funnel, add 23mL of 0.020g / mL potassium persulfate aqueous solution and 21mL of 0.213g / mL methyl allyl polyoxyethylene ether aqueous solution to the constant pressure dropping funnel respectively, seal the joints to form a closed experimental environment, replace the argon gas through a double row of tubes, pass condensed water into the reaction device, heat to 60℃ and stir for 30min, then add potassium persulfate aqueous solution dropwise for 30min, after the addition is complete, heat to 75℃, add methyl allyl polyoxyethylene ether aqueous solution dropwise for 25min, after the addition is complete, react for 5h, after the reaction is complete, add isopropanol to quench the reaction, purify, and obtain intermediate 5;
[0073] Q4: Add 0.85g of dodecyldimethylbenzyl ammonium chloride into 20mL of deionized water to dissolve it, pour it into a container, then dissolve 1.09g of intermediate product 5 in 20mL of deionized water, and slowly add it dropwise to the container for 35min. After the addition is complete, stir for 40min, let it stand for 48h, remove the supernatant, filter, wash, and vacuum dry at 50℃ and -0.1MPa for 24h to obtain intermediate product 6; mix 4g of intermediate product 4 and 0.81g of intermediate product 6 for 3h to obtain a composite photosensitizer.
[0074] This embodiment discloses a method for preparing an aldehyde reducing agent, comprising the following steps:
[0075] S1: Add 11 g corn starch to 52 mL distilled water and stir for 40 min to obtain a corn starch emulsion, which is then completely transferred to a three-necked flask with a constant pressure dropping funnel and a thermometer, and the beaker is placed in a constant temperature water bath at 60 °C for 30 min to obtain a viscous emulsion;
[0076] S2: Add 0.37 g of copper sulfate pentahydrate to the viscous emulsion, adjust the pH to 7, then add 8.5 mL of potassium permanganate dropwise, react at 60°C for 3 h, adjust the pH to 6, filter, wash, and vacuum dry at 60°C to obtain a formaldehyde reducing agent.
[0077] The present embodiment discloses an ecological self-hardening furan resin with controllable curing speed, which is composed of the following components in parts by weight: 38 parts of furfuryl alcohol, 15 parts of formaldehyde, 4 parts of urea, 4 parts of composite photosensitizer, 2.5 parts of formaldehyde reducing agent, 0.4 parts of silane coupling agent G-570, 0.25 parts of sodium hydroxide, 0.25 parts of hydrochloric acid, and 2.5 parts of nano silicon dioxide (Shanghai Yuanye Biotechnology Co., Ltd.).
[0078] This embodiment discloses a method for preparing an ecological self-hardening furan resin with controllable curing speed, comprising the following steps:
[0079] Step (1): heating formaldehyde and silane coupling agent G-570 at 60°C for 40 minutes, then adding urea, adjusting pH to 8 with sodium hydroxide, heating at 80°C for 45 minutes, then adding furfuryl alcohol, adjusting pH to 3 with hydrochloric acid, and heating at 110°C for 60 minutes to obtain a mixed reactant;
[0080] Step (2): Add a composite photosensitizer, a formaldehyde reducing agent and nano-silica to the mixed reactants, stir and react for 5 hours, and obtain an ecological self-hardening furan resin with controllable curing speed.
[0081] Comparative Example 1
[0082] Comparative Example 1 Compared with Example 1, in the process of preparing the composite photosensitizer in Comparative Example 1, no dibromotriphenylamine was added, and other conditions remained unchanged.
[0083] Comparative Example 2
[0084] Compared with Example 1, in Comparative Example 2, no corn starch was added during the preparation of the formaldehyde-reducing agent, and other conditions remained unchanged.
[0085] Comparative Example 3
[0086] Comparative Example 3 Compared with Example 1, in the process of preparing the ecological self-hardening furan resin in Comparative Example 3, no composite photosensitizer is added, and other conditions remain unchanged.
[0087] Comparative Example 4
[0088] Comparative Example 4 Compared with Example 1, in the process of preparing the ecological self-hardening furan resin in Comparative Example 4, no formaldehyde reducing agent is added, and other conditions remain unchanged.
[0089] Comparative Example 5
[0090] Comparative Example 5 Compared with Example 1, in the process of preparing the ecological self-hardening furan resin in Comparative Example 5, no nano-silicon dioxide is added, and other conditions remain unchanged.
[0091] The free formaldehyde content in the sample was tested according to the standard JB / T 7526-2008, and then 100g of the obtained samples were weighed and placed in the same container, and cured under light conditions of wavelengths of 220nm, 260nm, 300nm, 340nm, 440nm, 480nm, 520nm, 560nm, 620nm and 660nm, respectively. Other conditions such as humidity and light intensity remained the same. A stopwatch was used to measure the curing time and the curing rate was calculated. The operation was repeated 8 times. Under different light conditions, if the curing rate differed greatly, it means that the prepared sample has controllable curing performance. Subsequently, the sample cured under 480nm light conditions was selected, and the toughness test of the cured sample was performed using the standard GB / T 1451-2005. The test results are shown in Table 1:
[0092] Table 1
[0093]
[0094] It can be seen from the test results in Table 1 that the ecological self-hardening furan resin prepared by Examples 1-4 of the present invention has a controllable curing speed, high toughness and low free formaldehyde content. By comparing Comparative Example 1 with Examples 1-4, it can be seen that the addition of dibromotriphenylamine can make the obtained ecological self-hardening furan resin have a controllable curing speed; by comparing Comparative Example 2 with Examples 1-4, it can be seen that the addition of corn starch can make the obtained ecological self-hardening furan resin contain a lower free formaldehyde content; by comparing Comparative Example 3 with Examples 1-4, it can be seen that the addition of a composite photosensitizer can make the obtained ecological self-hardening furan resin have a controllable curing speed; by comparing Comparative Example 4 with Examples 1-4, it can be seen that the addition of a formaldehyde-reducing agent can make the obtained ecological self-hardening furan resin contain a lower free formaldehyde content; by comparing Comparative Example 5 with Examples 1-4, it can be seen that the addition of nano-silicon dioxide can make the obtained ecological self-hardening furan resin have higher toughness.
[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0096] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An ecological self-hardening furan resin with controllable curing speed, characterized in that: The invention is composed of the following components in parts by weight: 35-42 parts of furfuryl alcohol, 10-30 parts of formaldehyde, 2-8 parts of urea, 1-5 parts of composite photosensitizer, 1-3 parts of formaldehyde reducing agent, 0.2-0.5 parts of silane coupling agent, 0.2-0.4 parts of sodium hydroxide, 0.1-0.3 parts of hydrochloric acid, and 2-4 parts of nano silicon dioxide, wherein the composite photosensitizer is prepared from dibromotriphenylamine, bipyraclostrobin, 1-(4-bromophenyl)-pyrrolidine, malononitrile, sodium lignin sulfonate, potassium persulfate, methyl allyl polyoxyethylene ether and dodecyl dimethyl benzyl ammonium chloride, and the formaldehyde reducing agent is prepared from corn starch under the conditions of copper sulfate pentahydrate as a catalyst and potassium permanganate as an oxidant; The preparation method of the composite photosensitizer comprises the following steps: Q1: Under an argon atmosphere, phosphorus oxychloride was slowly added dropwise to N,N-dimethylformamide, the mixture was placed at room temperature and continued to be stirred, then dibromotriphenylamine was added, the temperature was raised to reflux, and after completion, the mixture was cooled, and then ice water was added to quench the reaction and stirred, allowed to stand, filtered, eluted, separated and purified to obtain intermediate 1; Q2: Under an argon atmosphere, add pinacol diboronate, 1-(4-bromophenyl)-pyrrolidine, potassium acetate and DPPF palladium dichloride to 1,4-dioxane in sequence, heat to reflux, cool, extract, dry, reduce pressure, elute, separate and purify to obtain intermediate product 2; under an argon atmosphere, mix intermediate product 1, intermediate product 2, DPPF palladium dichloride, cesium carbonate and anhydrous 1,4-dioxane, heat to reflux, cool, extract, elute, separate and purify to obtain intermediate product 3; under an argon atmosphere, add intermediate product 3 and malononitrile to dichloromethane, and simultaneously add triethylamine dropwise, heat the obtained mixture to reflux, elute, separate and purify to obtain intermediate product 4; Q3: Sodium lignin sulfonate was dissolved in distilled water and added to a three-necked flask connected to a constant pressure dropping funnel. A potassium persulfate aqueous solution and a methyl allyl polyoxyethylene ether aqueous solution were added to the constant pressure dropping funnel respectively. The joints were sealed to form a closed experimental environment. Argon gas was replaced through a double row of tubes. Condensed water was introduced into the reaction device. The temperature was raised with stirring. Then, the potassium persulfate aqueous solution was added dropwise. After the addition was completed, the temperature was raised and the methyl allyl polyoxyethylene ether aqueous solution was added dropwise. After the addition was completed, the reaction was carried out. After the reaction was completed, isopropanol was added to quench the reaction. The reaction was purified to obtain an intermediate product 5. Q4: Add dodecyldimethylbenzyl ammonium chloride to deionized water for dissolution, pour into a container, then dissolve the intermediate product 5 in deionized water, slowly drop into the container, stir after the addition is complete, let stand to react, remove the supernatant, filter, wash, and vacuum dry to obtain the intermediate product 6; mix the intermediate product 4 and the intermediate product 6 to obtain a composite photosensitizer.
2. The ecological self-hardening furan resin with controllable curing speed according to claim 1, characterized in that: In the Q1, the molar ratio of phosphorus oxychloride, N,N-dimethylformamide and dibromotriphenylamine is (8.94-13.41): (21.55-32.33): (1-1.5), the temperature of N,N-dimethylformamide is 0-1°C, the stirring time is 1-2h, the reflux temperature is 100-110°C, the time is 5-7h, and the cooling time is 30-40min; in the Q2, the molar ratio of biboric acid pinacol ester, 1-(4-bromophenyl)-pyrrolidine, potassium acetate and DPPF palladium dichloride is (2-4): (1-2): (2-4): (3.3-6.6), the heating reflux temperature is 110-120°C, the time is 20-24h, the molar ratio of intermediate product 1, intermediate product 2, DPPF palladium dichloride and cesium carbonate is (1-2): (2.2-4.4): (0.1-0.2): (0.6-1.2), the heating reflux temperature is 90-100°C, the time is 18-20h, the molar ratio of intermediate product 3 and malononitrile is (1-2): (1-2), the heating reflux temperature is 40-50°C, and the time is 2-3h.
3. The ecological self-hardening furan resin with controllable curing speed according to claim 1, characterized in that: In the Q3, the dosage ratio of sodium lignin sulfonate, distilled water, potassium persulfate aqueous solution and methyl allyl polyoxyethylene ether aqueous solution is (10-12) g: (50-60) mL: (20-25) mL: (20-25) mL, the concentration of potassium persulfate aqueous solution is 0.020 g / mL, the concentration of methyl allyl polyoxyethylene ether aqueous solution is 0.213 g / mL, the heating and stirring temperature is 50-60°C, the time is 20-30 min, the time for adding potassium persulfate aqueous solution is 30-35 min, the heating temperature is 70-80°C, the time for adding methyl allyl polyoxyethylene ether aqueous solution is 25-30 min, and the reaction time is 3-5 h.
4. The ecological self-hardening furan resin with controllable curing speed according to claim 1, characterized in that: In the Q4, the mass ratio of dodecyldimethylbenzylammonium chloride and the intermediate product 5 is (0.80-1.00): (1.01-1.26), the dropping time is 30-40 min, the stirring time is 30-40 min, the standing time is 48-50 h, the vacuum drying temperature is 40-50 ° C, the time is 20-24 h, the pressure is -0.1~-0.08 MPa, the mass ratio of the intermediate product 4 and the intermediate product 6 is (2-5): (0.8-0.9), and the mixing time is 2-3 h.
5. The ecological self-hardening furan resin with controllable curing speed according to claim 1, characterized in that: The preparation method of the aldehyde reducing agent comprises the following steps: S1: Add corn starch to distilled water and stir to obtain corn starch emulsion, then transfer it completely to a three-necked flask with a constant pressure dropping funnel and a thermometer, and place the beaker in a constant temperature water bath for constant temperature treatment to obtain a viscous emulsion; S2: Add copper sulfate pentahydrate to the viscous emulsion, adjust the pH and then add potassium permanganate dropwise, react at a constant temperature, adjust the pH, filter, wash, and vacuum dry to obtain a formaldehyde reducing agent.
6. The ecological self-hardening furan resin with controllable curing speed according to claim 5, characterized in that: In the S1, the dosage ratio of corn starch to distilled water is (10-13) g: (50-60) mL, the stirring time is 30-40 min, the constant temperature treatment temperature is 50-60°C, and the treatment time is 10-30 min. In the S2, the dosage ratio of copper sulfate pentahydrate to potassium permanganate is (0.3-0.5) g: (8-10) mL, the pH is adjusted to 7-7.5, the constant temperature reaction temperature is 50-60°C, the time is 2-3 h, and then the pH is adjusted to 6-6.5, and the vacuum drying temperature is 50-60°C.
7. A method for preparing an ecological self-hardening furan resin with controllable curing speed as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): heating formaldehyde and a silane coupling agent for mixed reaction, then adding urea, adjusting the pH with sodium hydroxide, heating to continue the reaction, then adding furfuryl alcohol, adjusting the pH with hydrochloric acid, and continuing the heating to react to obtain a mixed reactant; Step (2): adding a composite photosensitizer, a formaldehyde reducing agent and nano-silicon dioxide to the mixed reactants, stirring and reacting, and obtaining an ecological self-hardening furan resin with controllable curing speed.
8. The method for preparing the ecological self-hardening furan resin with controllable curing speed according to claim 7, characterized in that: In the step (1), the heating and mixing reaction temperature is 40-60°C, the time is 20-40 minutes, the pH is adjusted to 8-10, the heating and continued reaction temperature is 70-90°C, the time is 30-45 minutes, the pH is adjusted to 3-5, and the heating and continued reaction temperature is 80-120°C, the time is 40-60 minutes; in the step (2), the stirring reaction time is 3-5 hours.
Citation Information
Patent Citations
A kind of graphene-modified furan resin and preparation method thereof and furan resin glass fiber reinforced plastics
CN104448179B
Additive manufacturing rapid forming furan resin and preparation method thereof
CN112142936A
Benzophenone-modified triphenylamine pyridinium organic photosensitizer as well as preparation method and application thereof
CN117534611A
Cited By
Graphene oxide composite modified furan resin and preparation process thereof
CN122541660A